Vietnamese Pronunciation - Liem, Nguyen Dang (PALI Language Texts-Southeast Asia, 1970)
This is the first in the PALI Language Text series to deal with a Southeast Asian language. The author's approach in this pronunciation guide owes much to the methodology pioneered by Charles Fries. A basic assumption of this approach is that in learning a new language the problem is not first of all learning vocabulary but "mastery of the sound system." Moreover, the problems of learning a new sound system vary with the native language of the student. This manual is designed specifically for the English-speaking student and concentrates on the particular difficulties an English-speaking person would have in learning to speak Vietnamese. There are no outstanding grammatical differences in the three main Vietnamese dialects, but there are some significant phonological differences. The Saigon dialect forms the main core of the lessons here, but materials and drills of standard Hanoi Vietnamese have been included in review lessons for recognition purposes.